2002
DOI: 10.3397/1.2839672
|View full text |Cite
|
Sign up to set email alerts
|

Insufficiency of an environmental sound's power spectrum as a predictor of its annoyance

Abstract: The annoyance of environmental noise exposure and its "acceptability" with respect to land use compatibility and other interpretive criteria are routinely assessed in terms of assorted frequencyweighted noise metrics. Although laboratory measurements have established the utility of frequency-weighting networks and more complex procedures as predictors of the judged annoyance of sounds heard under controlled listening conditions, many factors can erode the predictive utility of noise metrics in residential sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
2
1
Order By: Relevance
“…Intriguingly, the result, replicated three times, that our transformed noise samples were less annoying than the identifiable ones, is at odds with earlier findings by Fidell et al (2002), Ellermeier et al (2004) and Zeitler et al (2004), who reported more annoyance for unidentifiable compared to identifiable sound samples. The samples used for the latter two articles were, however, everyday noises (e.g., a bouncing coin, a toilet flushing and sound from a coffee maker).…”
Section: General Discussion and Conclusioncontrasting
confidence: 82%
See 2 more Smart Citations
“…Intriguingly, the result, replicated three times, that our transformed noise samples were less annoying than the identifiable ones, is at odds with earlier findings by Fidell et al (2002), Ellermeier et al (2004) and Zeitler et al (2004), who reported more annoyance for unidentifiable compared to identifiable sound samples. The samples used for the latter two articles were, however, everyday noises (e.g., a bouncing coin, a toilet flushing and sound from a coffee maker).…”
Section: General Discussion and Conclusioncontrasting
confidence: 82%
“…Another explanation could be that their samples were relatively short compared to ours-which means that their unrecognizable, neutralized noise samples were as well. This was also the case, but less so for Fidell et al (2002), who used samples of 8 s. In their experiment several transportation noises have been used as well. It is possible that short outbursts of unrecognizable sounds or pink noise are perceived as more annoying or threatening than the original sounds itself.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation